Analysis Of Agrarian Conflict 2023 On Rempang Island Riau Islands In Laswellian Perseptive - Hayatun Nufus; Jamalullail Jamalullail; Mira Natalia Pellu; Marwan Hadi; Wahyu Adi Setyo Wibowo (LPPM Universitas PGRI Sumatera Barat, 2023)
The agrarian conflict on Rempang Island, Riau Archipelago Province, reflects structural issues involving indigenous communities, the government, and investors in the context of the Rempang Eco-City development. This study analyzes the conflict using Harold Lasswell's (1936) political communication perspective on